Inflammatory and immunogenic response of the tissue after application of freeze-dried hydroxyapatite gypsum puger scaffold compared to freeze-dried hydroxyapatite bovine scaffold - Amiyatun Naini; Mohamad Rubianto; Fourier Dzar Eljabbar Latief; Achmad Gunadi; Dewi Kristiana; Nike Hendrijantini; I Ketut Sudiana (Wolters Kluwer Medknow Publications, 2020)
Background: Inflammation is a mechanism or reaction of the natural immune system to defend from external hazards. All foreign objects that enter the body will trigger an immune response in the form of antibodies. In Indonesia, the prevalence of diseases that involve the inflammatory process in the body is high. Freeze-dried hydroxyapatite gypsum puger (HAGP) scaffold is a gypsum powder which is currently under development as a bone replacement material. Freeze-dried hydroxyapatite bovine (HAB) scaffold is a bone substitute material available on the market. Objective: To analyze the inflammatory and immunogenic responses in the tissue after application of freeze-dried HAGP scaffold compared to freeze-dried HAB scaffold through mediators of tumor necrosis factor alpha (TNF-α) and immunoglobulin G (IgG) in rats. Materials and Methods: This study used Wistar rats. HAGP group and HAB group were applied subcutaneously, settled for 7 and 14 days, then the levels of TNF-α and IgG were measured using enzyme-linked immunosorbent assay. Statistical analysis was done using nonparametric test with the Kruskal-Wallis test. Results: TNF-α levels at day 7 in the HAGP group were nearly equal to the control group, while those in the HAB group were higher. Statistically, the significance was P = 0.184 (P > 0.05). At the 14th day, the level of IgG on the HAGP and HAB groups the level was higher than the control group, statistically it was found P = 0.127. Conclusion: freeze-dried HAGP scaffold compared to freeze-dried HAB scaffold did not cause inflammatory and immunogenic response on rats through mediators of TNF-α and IgG.